The Impact of Motivation on Retention of Employee in Radisson Hotel, Kathmandu - KC, Rajat; Jha, Suvita (Kathford Journal of Engineering and Management, 2025)
Employee retention is critical for every organization, and this research aims to examine the impact of motivation on employee retention in the service industry, specifically at Radisson Hotel, Kathmandu. A causal-comparative research design was employed to explore the cause-and-effect relationship between motivation and retention. A self-administered questionnaire was used to collect the survey data for this study. Out of 250 employees, a sample size of 154 was selected, but only 101 valid responses were obtained through simple random sampling. The analysis utilized both descriptive and inferential methods. The study found that compensation and work environment positively impact retention, while work-life balance does not effectively motivate retention.